Increased heart rate with sleep disordered breathing in hypertrophic cardiomyopathy. (15th January 2021) - Konecny, Tomas; Khoo, Michael; Covassin, Naima; Edelhofer, Paul; Bukartyk, Jan; Park, Jae Yoon; Venkataraman, Shreyas; Karim, Shahid; Chahal, Anwar; Kara, Tomas; Orban, Marek; Ludka, Ondrej; et al.
Abstract: Background: Current guidelines recommend medications with rate control properties for symptomatic patients with hypertrophic cardiomyopathy (HCM) based on the rationale that lowering heart rate (HR) improves their symptoms. Whether sleep disordered breathing (SDB) is associated with increased HR in HCM patients is not known. Method: We diagnosed uncontrolled SDB (oxygen desaturation index ≥5) in consecutive echocardiographically confirmed HCM patients seen at Mayo Clinic, Rochester, and analyzed their HR as recorded by a 24-h Holter monitor. We compared mean, minimum, maximum HR between those with vs without SDB. In a pilot subanalysis of HCM patients with SDB who also underwent subsequent diagnostic polysomnography (PSG), we analyzed RR interval changes coinciding with obstructive sleep apnea and hypopnea episodes. Results: Of the 230 HCM patients included in this study (age 54 ± 16 years; 138 male; LVOT pressure gradient at rest 45 ± 39 mmHg), 115 (50%) patients had SDB. HCM patients with SDB were recorded to have higher mean HR (71 vs. 67 bpm; p  = .002, adjusted p  = .001), and this difference was most pronounced during night hours of 10 PM to 5 AM (61 vs. 67 bpm; p  < .001). In the pilot analysis of the available PSG data, the release of obstructive sleep apneas and hypopneas coincided with fluctuation of HR. Conclusions: SDB is independently associated with higher mean HR in patients with HCM, and this difference is most significant during sleep. Treatment of SDB, which is readily available, should be tested as a complementary modality to the currently recommended pharmacotherapy aimed at lowering HR in patients with symptomatic HCM. Highlights: Hypertrophic cardiomyopathy patients with sleep apnea have higher mean heart rate This difference is most pronounced during night-time hours. Further studies could explore whether sleep apnea treatment could complement rate-control medications in symptomatic patients.